Comparative analysis of the medicinal and nutritional components of different varieties of Pueraria thomsonii and Pueraria lobata - Fu, Mei; Jahan, Mohammad Shah; Tang, Kang; Jiang, Shizheng; Guo, Juxian; Luo, Shanwei; Luo, Wenlong; Li, Guihua (Frontiers in Plant Science, 2023)
Pueraria thomsonii and Pueraria lobata are important medicinal plants with unique chemical compositions that are widely used in traditional Chinese medicine. To compare the nutritional and medicinal profiles of these two species, we analyzed the flavonoid, dietary fiber, total starch, and crude protein contents of one P. lobata and three P. thomsonii varieties using ultra-performance liquid chromatography-tandem mass spectrometry, enzyme weight, acid hydrolysis, and Kjeldahl methods. Furthermore, we used principal component analysis and hierarchical clustering heatmap analysis to separate the data obtained from the P. thomsonii and P. lobata samples. We detected 279 flavonoid compounds in the two Pueraria species, including 90 isoflavones and 78 flavonoids. A large proportion of isoflavones and flavonoids were more abundant in P. lobata than in P. thomsonii. The total starch content was significantly higher in P. thomsonii than in P. lobata. By contrast, the soluble dietary fiber, insoluble dietary fiber, and crude protein contents were substantially lower in P. thomsonii than in P. lobata. Taken together, our results demonstrate that P. lobata is better suited for use as a medicine, whereas P. thomsonii is better suited as an edible food, and provide a theoretical foundation for developing P. thomsonii and P. lobata germplasm resources.